The Examination of Relationship Between the Approaches to Environmental Ethics and Environmental Behaviours of Teacher Candidates by Different Variables - Mehpare Saka (Journal of Education in Science, Environment and Health)
The aim of this study is to determine the environmental behaviour and the approaches to environmental ethics of teacher candidates whether or not they differ in terms of gender, department and place of residence. Moreover, the relationship between the approaches to environmental ethics of teacher candidates and their environmental behaviours was established and interpreted in the study. The research group of the study, in which screening model is used, consists of 881 third year and final year student teachers from the departments of science teaching, primary school teaching and social sciences teaching in five state universities. Out of the teacher candidates, 650 are female and 231 are male students. The data were obtained with Environmental Behaviour Scale and the Approaches to Environmental Ethics Scale. Descriptive statistics, Mann Whitney-U and Kruskal-Wallis H tests, and Spearman Rank-Difference Coefficient of Correlation methods were used for the analysis of the data which determined that there was a low level of relationship between the environmental behaviours and the approaches to environmental ethics of the teacher candidates and that the approaches to environmental ethics and the environmental behaviours differed for some of the variables including gender, department and place of residence.